Вибір раціонального енергетичного засобу для агрегатування мобільного змішувача-кормороздавача - Болтянський, Борис Володимирович; Болтянский, Борис Владимирович; Boltianskyi, Borys; Парієв, А. О.; Дереза, Олена Олександрівна; Дереза, Елена Александровна; Dereza, Olena; Дереза, Сергій Володимирович; Дереза, Сергей Владимирович; Dereza, Serhii; Дробишев, О. О.; Коротченко, Т. М. (ТДАТУ, 2020)
UK: В статті проводиться аналіз технологічного процесу підготовки компонентів з раціону годування великої рогатої худоби і їх видачі у вигляді кормосуміші. Найбільш ефективно цей процес проводити за допомогою змішувачів-кормороздавачів з вертикальними робочими органами – шнеками. Загальна необхідна потужність на функціонування такого кормороздавача-міксера буде складатись із суми потужностей на його транспортування, приготування кормосуміші і вивантаження готової кормосуміші на кормовий стіл у тваринницькому приміщенні. Виведена аналітичним шляхом формула знаходження загальної потужності дозволить раціонально підходити до вибору енергетичного засобу для агрегатування мобільного змішувача-роздавача з вертикальним шнеком. RU: В статье проводится анализ технологического процесса подготовки компонентов из рациона кормления крупного рогатого скота и их выдачи в виде кормосмеси. Наиболее эффективно этот процесс проводить с помощью смесителей-кормораздатчиков с вертикальными рабочими органами - шнеками. Общая требуемая мощность на функционирование такого кормораздатчика- миксера будет состоять из суммы мощностей на его транспортировку, приготовление кормосмеси и выгрузку готовой кормосмеси на кормовой стол в животноводческом помещении. Выведенная аналитическим путем формула нахождения общей мощности позволит рационально подходить к выбору энергетического средства для агрегатирования мобильного смесителя-раздатчика с вертикальным шнеком. EN: At present, farms are switching to modern resource-saving technologies for milk and meat production through the use of new technological solutions for keeping, feeding, watering, caring for and exploiting livestock. The issues of energy saving and energy efficiency are becoming more and more relevant every year. The organization of the process of preparation for feeding and distribution of feed is one of the sources of reducing the cost of livestock products, and therefore is a way to save energy. This process consumes 2.5 – 2.8 GJ of fuel and lubricants per capita during the year. The search for ways to reduce the energy intensity of this process is continuously associated not only with the technology of preparation of feed for feeding, the choice of technological means for the distribution of feed, but also with the choice of energy for aggregation of these means. The article analyzes the technological process of preparation of components from the diet of cattle and their issuance in the form of feed. It is most effective to carry out this process by means of mixers-feeders with vertical working bodies - screws. The total required capacity for the operation of such a feed mixer will consist of the sum of the capacities for its transportation, preparation of the feed mixture and unloading of the finished feed mixture on the feed table in the livestock room. Analysis of the obtained formula shows that to determine the required power to drive the mixer-feeder it is necessary to know the following initial data: the composition of the feeding ration, physical and mechanical properties of feed components (bulk, external friction angle) and technical characteristics of the feeder (hopper size, radius and auger speed). The formula of finding the total capacity derived by analysis will allow to rationally approach the choice of energy means for aggregation of the mobile mixer-distributor with a vertical auger.
Выбор рационального энергетического средства для агрегатирования мобильного смесителя-кормораздатчика
Choice of rational energy means for aggregation of mobile mixer-feeder
Keywords: скотарство; кормосуміш; кормороздавач; змішувач; міксер; бункер; потужність; енергетичний засіб; шнек; скотоводство; кормосмесь; кормораздатчик; смеситель; миксер; бункер; мощность; энергетическое средство; шнек; livestock; feed mixture; feed dispenser; mixer; bunker; power; energy; auger